Impact of trigger factors on clinical profile of migraine patients - Banday, Muddasir Sharief; Wani, Maqbool; Para, Bilal Ahmad; Qureshi, Sabia (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Migraine is a primary headache disorder. The study was designed to provide a better understanding of the potential role of triggers in the cause of migraine and their impact on its clinical profile and treatment protocol. Methods: A prospective study was conducted between June 2018 to May 2020 in 323 patients suffering from migraine in out-patient department of neurology. Patients were labelled as migraine on the basis of simplified diagnostic criteria for migraine. A structured questionnaire was used to interview patients about triggers and correlated with various clinical variables. Results: All patients had migraine without aura with males 30 (9.3%) and females 293 (90.7%). Episodic migraine found more than chronic daily headache. Trigger factors were present in 234 (72.4%) and absent in 89 (27.6%) patients. Common triggers were hot climate, emotional stress, lack of sleep and fasting. Common foods to precipitate an attack are tomatoes, cheese and collard greens. Mean duration of headache in patients with trigger factors is 5.67±4.99 years with a significant p value (p<0.02). Mean frequency of headache in trigger positive patients is 15.22±8.28 (days/month). Clinical symptoms significant in trigger positive patients are nausea (p<0.0001) (OR=3.94;95% CI=2.02-7.68),vomiting (p=0.0001) (OR=2.62;95% CI=1.50-4.59), photophobia (p<0.0001) (OR=2.69;95% CI=1.56-4.64), phonophobia (p<0.0001) (OR=5.16; 95% CI=2.54-47), pulsating headache (p=0.006) (OR=2.09; 95% CI=1.22-3.56), unilateral location (p<0.0001) (OR=2.88; 95% CI=1.74-4.77). Conclusions: Triggers are not easily modifiable, and avoiding triggers may not be realistic. Healthy life style like exercise, adequate sleep, stress management and eating regularly may prevent triggers and transformation to chronification over time.